Analysis of the behavior of an all-optical not logic gate in a photonic crystal directional coupler / Análise do comportamento de uma porta lógica not totalmente óptica em um acoplador direcional de cristal fotônico - Oliveira, Jorge Everaldo de (2022)
In the present work, an optical directional coupler (ODC) based on two-dimensional (2-D) photonic crystal (PhC) was analyzed and proposed, through the methods of plane wave expansion (PWE) and finite-difference time-domain (FDTD), which were used with the purpose of analyzing the behavior of a new all-optical NOT logic gate and the electric field distribution in the coupler for linear (bar), non-linear (cross) states and the control signal. The simulation results in OptiFDTD software show that the proposed crystal structure is a strong candidate for use in ultrafast photonic integrated circuits (PICs), being highly advantageous with excellent transmission performance and simple design.